Vanishing acts - Barker, Brian, 1973- (Crab Orchard award series in poetry., 2019)
"In "Vanishing Acts" the poems straddle the comic and the tragic. They are by turns funny and haunting and ripe with scathing satire. They draw on the genres of the speculative and science fiction as much as our poetic traditions and speak to the precarious state of man and the natural world in the twenty-first century"--